The effect of forest cover for the dynamics of a snowpack : linking snow water equivalents, meltwater contributions and evaporative loss - Millán, Álvaro Valle (SLU/Dept. of Forest Ecology and Management, 2010)
Forestry is one of the main economical activities in Sweden, but it can seriously affect the dynamic of the water cycle by altering several hydrological factors such as timing and amount of snow melt and meltwater contributions from the snowpack to the soil.